Trade and Natural Disasters: The Role of Institutional Quality on APEC's Exports - Leonardo, Stella (Gorontalo State University, 2025)
This paper examines how natural disasters affect exports of the Asia Pacific Economic Cooperation (APEC) economies including how institutional quality (government effectiveness) plays a role in the export flows after natural disasters hit the economies. While various literatures have identified these issues separately, this research would like to fill this gap by exploring the linkages between exports, natural disasters, and institutional quality. The analysis in this paper is based on the gravity model theory which used exports, natural disasters, and the government effectiveness index data from 2003-2022. Overall, the results show that natural disasters have a negative association with the export flows from APEC both at the time when natural disasters hit and in the following year. Having the government effectiveness index above the APEC's average has positively counteracted the negative effect caused by natural disasters, particularly when devastating catastrophes hit the economies. The findings in this paper are relevant for APEC economies that are prone to experience natural disasters, but they need economic growth, particularly from exports. Some policy implications can be drawn from these results such as in the area of export strategies, improving government effectiveness, and disaster preparedness. The key message here is to encourage the APEC economies which are vulnerable to face natural disasters, to keep maintaining a positive export performance through improving the government effectiveness.